PENINGKATAN KINERJA SUMBER DAYA MANUSIA MELALUI MOTIVASI, DISIPLIN, LINGKUNGAN KERJA, DAN KOMITMEN: Studi Kasus di PT. Korindo Heavy Industri, Tangerang, Banten - Abdul Aziz Aziz (NIAGARA Scientific Journal, 2023)
This research aims to analyze the performance of PT employees. Korindo Heavy Industry, Tangerang Banten. This research uses motivation, discipline and work environment variables to analyze the influence on performance. Apart from that, this research also uses commitment as an intervening variable to analyze the influence of the level of commitment on the company. The population in this study were employees of PT. Korindo Heavy Industry. This population is 110 employees. This research uses a census method, namely by giving questionnaires to the entire population of 110 employees. Data collection was carried out using the questionnaire method, namely by giving a list of questions or questionnaires directly to respondents. The data analysis technique in this research uses SEM (Structural Equation Model) analysis which is operated through the SMARTPLS program. The research results show that the variables of motivation, discipline and work environment have a significant positive effect on commitment. The variables motivation, discipline, commitment and work environment show a significant influence on positive results on human resource performance.